Architecting Hybrid Edge-Cloud Solutions: Integration Patterns for Public Cloud Platforms - Gokul Chandra Purnachandra Reddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the integration of edge computing with major public cloud platforms, presenting a structured analysis of architectural patterns, implementation challenges, and optimization strategies in this rapidly evolving technological domain. The article explores three fundamental integration models—hub-and-spoke, mesh, and hybrid patterns—evaluating their suitability for various use cases and operational environments. It explores critical implementation challenges related to connectivity management, data synchronization, security architecture, and resource orchestration, offering practical solutions for each area. The article analyzes edge computing approaches from major cloud providers, including AWS, Azure, and Google Cloud, highlighting their strengths and limitations. Through case studies across manufacturing, retail, healthcare, and smart city applications, the article demonstrates the transformative impact of edge-cloud integration on performance metrics and business outcomes. The article concludes with a decision framework for architectural pattern selection, best practices for successful deployment, and an examination of emerging technologies that will shape the future of distributed computing architectures.
Keywords: Edge Computing; Cloud Integration; Distributed Architecture; Hybrid Deployments; Workload Optimization